ANALISIS PENERJEMAHAN FRASE: STUDI KASUS PADA PENERJEMAHAN FRASE BAHASA JEPANG KE BAHASA INDONESIA OLEH MAHASISWA STBA YAPARI-ABA BANDUNG - Yayat Hidayat; Asteria Martawijaya (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2018)
Personal name is a kind of identity that always sticks on one’s personality forever. Moreover, it shows the identity of community. From the personal name we can indicate the language and the culture of certain community. Start from that reason, this research tries to answer the problem about the system of French personal name. The data of this research are the personal names of French people who live in France. The system of French personal name consist of: first name and surname. Besides, there is a recurring element but it doesn’t have to exist, it called particule. To manage the personal name in France, the government draws it up in a law, especially for surname. Talking about surname, French personal name is original. Etymologically, French personal name is devised into: group of vegetation, profession, physical characteristics, places, animals, and object.